Transvaginal natural orifice transluminal endoscopic surgery for ectopic pregnancy. Issue 3 (24th January 2022) - Ozceltik, Gokay; Simsek, Deniz; Hortu, Ismet; Yeniel, Ahmet O.; Itil, Ismail M.
Abstract: Aims: This study aims to describe our transvaginal natural orifice transluminal endoscopic surgery (vNOTES) technique for ectopic pregnancy that can be performed using conventional laparoscopic equipment with the addition of a self‐constructed pessary port and to evaluate the safety, feasibility, and outcomes of the technique. Methods: This is a retrospective study evaluating outcomes of patients who underwent vNOTES for ectopic pregnancy ( n  = 21) between August 2019 and April 2021. Results: Twenty‐one patients underwent vNOTES as intended without any intraoperative complications. Three patients (14.3%) were nulliparous, 16 patients (76.2%) had no history of vaginal delivery, and 13 patients (61.9%) had a history of at least one cesarean delivery. Eight patients (38.1%) had a history of previous abdominal surgery other than cesarean section. The mean duration of surgery was 43.4 ± 12.6 min. The mean visual analog scale scores for pain were 2.45 ± 1.13 at 2 h after surgery, 0.45 ± 0.83 at 12 h after surgery, and 0.18 ± 0.36 at 24 h after surgery. The median duration of postoperative hospital stay was 1 day (range, 1–2). There were no postoperative complications within 30 days after surgery. Conclusions: vNOTES can be performed in an existing laparoscopy setup with the addition of a self‐constructed pessary port. vNOTES is a safe and effective surgical treatment option for ectopic pregnancy, even in patients who have not had a vaginal delivery and have had multiple abdominal surgeries.